Tooth contact analysis of crown gear coupling with misalignment. (August 2018) - Guan, Yabin; Fang, Zongde; Yang, Xiaohui; Chen, Guoding
Highlights: The generating principles and geometry of crown gear coupling are proposed. An accurate model is presented to analyze crown gear coupling meshing. Crowning depends on displacement circle radius. The effects of misalignment and crowning on tooth contact are discussed. Abstract: In this paper, manufacturing methods are presented for crown gear coupling composed of a hub with longitude crowning and tip sphere teeth, and a sleeve with straight internal teeth. Complete geometrical mathematical models of tools are proposed, including the flank and tip fillet regions. The flank and root fillets of the hub and sleeve generated by the cutters are obtained based on the theories of differential geometry and gear mesh. An accurate method based on a tooth contact analysis technique is presented to determine the contact points (locations of the maximum interference or minimum clearance) and to analyze the crown gear coupling meshing with angular misalignment. In addition, the effects of misalignment angle and crowning depending on the displacement circle radius on the maximum interference, interference distribution and locations of the maximum interference in every angular position of the hub are discussed with an example. It is observed that the side edge contact of the hub tooth can be avoided by modifying the misalignment angle or displacement circle radius and that the location of the maximum value of the maximum interference during one rotation cycle of the hub tooth is around the pure tilted area.